1.zapisz nie uzywajac nawiasów
a)-(-a)+(-b)
b)-(-a)-(-b)
c)a+(-(-b))
d) a-(-(-b))
e) -(-(a-b))
f) a-(b-a)
2.wstaw nawiasy
a) 3x-2y+1-x+y=2x-3y+1
b) 4m+2n-3+m-n+1=5m+n-4
c)-2t+u-w+1+w=-3t+u+1
d) -3x²-2x-1-5x²+3-7x²-3x=5x²+x+4
3.wpisz brakujace wspolczyniki
4a(3x-0,5y)=...ax-...ay
2k(3m-1,5n)=...km-...kn
3s(2s+4t)=...s²+...st
-2x²(-5x-4)=...x³+...x²
4.uzupełnij
a) 2x(3y+...)=...+12x²
b) 5t²(...-0.2rt)=t²-...
c)-½y(2y²+...)=...-4y
d)...-2ab² a w mianowniku 8=2ab-...
e) kn(...-n)=-k²n-...
f)...*(3xy-2t)=6x²y-...
g)½a(4a²b²-...)=...-a³
h) 3t²+...a w mianowniku -6=...-⅓

1

Odpowiedzi

2010-01-11T19:59:35+01:00
1.
a) a-b
b) a+b
c) a+b
d) a-b
e) a-b